Culture of the People of Central Asia in the V-XII Centuries - Markova G. V. (European Journal of Life Safety and Stability (2660-9630), 2023)
The article is topical, devoted to the analysis and development of the culture of the peoples of Central Asia since ancient times. One of the most important laws operating throughout the history of world culture is continuity. Each new stage in the process of the historical development of culture, negating the previous one, includes all its progressive content, all that has been acquired by mankind at the preceding stages. Humanity, climbing the ladder of historical progress, passing from one civilization to another, moving within each given civilization, does not create anew its material and spiritual culture each time, but relies on the results previously achieved.